Temporal trends in voluntary behavioural changes during the early stages of the COVID-19 outbreak in Japan. (March 2021) - Kashima, Saori; Zhang, Junyi
Abstract: Objectives: This study evaluated the characteristics of individuals with voluntary behavioural changes (cancellation and postponement of bookings) during the early stages of the coronavirus disease 2019 (COVID-19) outbreak in Japan. In addition, the temporal trends of these changes were captured. Study design: A cross-sectional analysis and a time series analysis were conducted. Methods: A nation-wide retrospective panel survey was conducted at the end of March 2020 (n = 1052). Odds ratios for cancellations/postponements with respect to individual characteristics were calculated in the analysis. To determine the temporal trend, the incidence ratios were compared throughout the time series analysis for four time periods: period 1, before the announcement of the Public Health Emergency of International Concern (PHEIC) from the World Health Organisation (WHO) (January 1–31); period 2, after the announcement of PHEIC (February 1–26); period 3, after the announcement of school closures by the Japanese government (February 27 – March 11); and period 4, after the announcement of the pandemic by the WHO (March 12–31). Results: In total, 72% of respondents cancelled or postponed their bookings at least once, and about half of the changes occurred in period 3. Elderly individuals' changes in gatherings were, on average, 5.9 times (95% confidence interval [CI] 1.9– 17.9) higher than those of young individuals. The incidence rate of change in gatherings during period 3 was 7.11 times (95% CI: 5.16– 9.81) higher than in period 2 and 3.15 times (95% CI: 2.25– 4.43) higher than in period 4. Significant interaction terms were observed in age and residential city size, but not sex, of the respondents. Conclusions: A significant proportion of the Japanese population voluntarily changed their behaviour during the early stages of the COVID-19 outbreak, and the government's announcement of school closures was a key trigger during this time. Graphical abstract: Image 1 Highlights: Temporal behavioural changes for the coronavirus disease 2019 outbreak in Japan were evaluated. A high percentage of the population had voluntarily initiated behavioural changes. Differences in behavioural changes were observed across individual characteristics. The government announcement for school closures was a key trigger for behavioural change across all ages. Significant interaction effects between time periods and characteristics were observed.